High-toughness weather-resistant hdpe bridge cable sheath material and preparation method thereof
Patent Information
- Application Number
- CN202611121512.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-20
AI Technical Summary
[0004]为了改善护套长期使用出现磨损,进而影响使用寿命的问题,本申请提供了一种高韧耐候HDPE桥梁缆索护套料及其制备方法
1、本申请中上述多种组分协同配合,抵消短板,制备的护套料同时具备优异低温韧性、低成型收缩、长效耐紫外老化、无卤阻燃、抗弯折疲劳等多重性能,适配大跨度桥梁缆索的要求,克服传统单一 HDPE 护套低温易裂、耐候差、无阻燃、尺寸易变形等缺陷。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the technical field of insulating sheaths, and in particular to a high-toughness, weather-resistant HDPE bridge cable sheath material and its preparation method. Background Technology
[0002] The stay cables, suspenders, and main cables of long-span cable-stayed bridges, suspension bridges, and arch bridges are the core load-bearing components of the bridge, directly determining the overall service safety of the bridge. The outer layer of the cable wires generally uses a high-density polyethylene (HDPE) hot-extruded sheath as the first line of corrosion protection, preventing rainwater, salt spray, ultraviolet rays, and industrial corrosive media from penetrating the steel wires and avoiding rust and breakage. Once the sheath cracks, powders, or breaks, corrosive media will quickly erode the steel strands, significantly shortening the cable's service life.
[0003] In existing technologies, the raw materials for the sheath generally include high-density polyethylene resin, antioxidants, light stabilizers, carbon black, EVA (ethylene vinyl acetate), and polyethylene wax. These raw materials are mixed and melt-extruded to obtain the sheath. Under strong winds, the cable vibrates continuously, and the sheath rubs against the steel structure and adjacent cables for extended periods. This results in a high coefficient of friction and significant wear, leading to scratches and surface peeling within a short time, compromising the protective integrity and consequently affecting the sheath's service life. Summary of the Invention
[0004] To address the issue of wear and tear on the sheath during long-term use, which affects its service life, this application provides a high-toughness, weather-resistant HDPE bridge cable sheath material and its preparation method.
[0005] This application provides a high-toughness, weather-resistant HDPE bridge cable sheath material, employing the following technical solution: A high-toughness and weather-resistant HDPE bridge cable sheath material, comprising the following raw materials by weight: 50-55 parts high-density polyethylene, 8-10 parts POE ethylene-octene copolymer elastomer, 4-6 parts wollastonite, 3-4 parts carbon black masterbatch, 1-2 parts ultraviolet absorber, 2-3 parts antioxidant 1010, and 5-7 parts flame retardant.
[0006] By adopting the above technical solution, high-density polyethylene (HDPE) serves as the main body of the sheath material, providing basic structural strength, rigidity, heat resistance, and excellent electrical insulation. The regular molecular chains and high crystallinity of HDPE give it good tensile strength and resistance to environmental stress cracking, forming the basis for bearing the cable's own weight and external loads. POE (ethylene-octene copolymer elastomer) can be uniformly dispersed in the HDPE matrix to form an elastic toughening phase, effectively absorbing and dispersing impact energy. This significantly improves the material's elongation at break and low-temperature performance, and enhances its bending fatigue performance, making the cable less prone to cracking under long-term vibration and repeated bending.
[0007] Wollastonite enhances rigidity and dimensional stability, increases flexural modulus and heat distortion temperature, making the sheath less prone to warping and deformation under long-term sunlight exposure and load. It also improves the material's wear resistance, compressive strength, and creep resistance, allowing it to withstand the cable's own weight and long-term wind pressure without deformation. Carbon black masterbatch efficiently absorbs and scatters ultraviolet light, preventing polymer chains from breaking and degrading due to UV excitation. This gives the sheath a black appearance, masks filler color differences, and provides dust and dirt resistance, significantly extending the sheath's service life under outdoor exposure.
[0008] UV absorbers capture active free radicals generated by UV excitation, blocking the photoaging chain reaction. Working synergistically with the physical shading effect of carbon black, they provide dual protection, significantly delaying the powdering, embrittlement, and mechanical degradation of the sheath after long-term outdoor exposure, thus extending the service life of the bridge cable sheath. Antioxidant 1010 prevents the thermal oxidative degradation of HDPE during the high-temperature melting process of the sheath. During long-term outdoor use, it continuously captures peroxide free radicals generated by heat and light, delaying yellowing and embrittlement. Flame retardants slow down combustion and inhibit flame spread when exposed to open flames or high temperatures, meeting the fire safety standards for bridge cables.
[0009] The above-mentioned components work synergistically to offset shortcomings, and the prepared sheath material has multiple properties such as excellent low-temperature toughness, low molding shrinkage, long-term UV aging resistance, halogen-free flame retardancy, salt spray corrosion resistance, bending fatigue resistance, and long-term creep resistance. It is suitable for the requirements of long-span bridge cables and overcomes the defects of traditional single HDPE sheaths such as easy cracking at low temperatures, poor weather resistance, lack of flame retardancy, and easy dimensional deformation.
[0010] Preferably, the high-density polyethylene is treated with calcium sulfate whiskers and molybdenum disulfide nanoparticles.
[0011] By adopting the above technical solution, calcium sulfate whiskers are fibrous single crystals with high tensile strength and high elastic modulus. They play a reinforcing role in HDPE similar to steel bars, effectively improving the tensile strength, flexural strength and modulus of HDPE. Calcium sulfate whiskers are dispersed in the HDPE structure, and their fibrous structure can bridge cracks like a bridge, effectively preventing crack propagation, thereby improving the material's impact resistance, and also improving the heat resistance and thermal decomposition temperature of HDPE.
[0012] Molybdenum disulfide nanoparticles exhibit superior friction-reducing and wear-resistant properties, significantly lowering the coefficient of friction and wear rate of HDPE, making the material more scratch-resistant and increasing the degradation temperature, crystallization peak temperature, and glass transition temperature of HDPE. Micron-sized calcium sulfate whiskers construct a macroscopic reinforcing framework, while nano-sized molybdenum disulfide provides microscopic lubrication and functional modification. Molybdenum disulfide nanoparticles fill the tiny gaps between the calcium sulfate whiskers and HDPE, improving interfacial compatibility, buffering stress concentration, and retaining the high low-temperature toughness imparted by POE while enhancing strength and dimensional stability, making it less prone to cracking under high and low temperature cycling. Ultimately, this results in HDPE composites possessing high strength, high rigidity, high wear resistance, and good thermal stability.
[0013] Preferably, the molybdenum disulfide nanopowder is pretreated with graphene and polyvinylpyrrolidone.
[0014] By employing the above technical solution, molybdenum disulfide nanoparticles possess a high specific surface area and abundant active edge sites, but strong van der Waals forces exist between the layers, making them prone to irreversible hard aggregation. The polar groups on the polyvinylpyrrolidone (PVP) molecular chain can be firmly adsorbed onto surface defects or edge sites of the PPVP nanoparticles. The long-chain molecules extend into the solution, forming a dense polymer brush layer, which effectively prevents the nanospheres from approaching each other through steric hindrance, achieving a monodisperse state. PPVP-modified PPVP nanoparticles can then better adhere to graphene sheets.
[0015] The long chains of polyvinylpyrrolidone (PVP) can not only adsorb molybdenum disulfide (MoD) nanoparticles, but their hydrophobic segments can also interact strongly with the conjugated surface of graphene through π-π stacking or van der Waals forces. This essentially bridges the gap between the MoD nanoparticles and graphene, ensuring a tight bond during subsequent composite formation. The uniformly dispersed MoD nanoparticles will deposit or anchor on the graphene sheet surface, preventing agglomeration between the MoD nanoparticles, enhancing the interfacial bonding between the composite filler and HDPE / POE resins, reducing filler-resin interface voids, and improving overall tensile and flexural strength without significantly sacrificing low-temperature toughness.
[0016] When these three components are combined, polyvinylpyrrolidone ensures that graphene is uniformly coated on the surface of molybdenum disulfide nanopowder. Graphene isolates the nanospheres and improves the resin interface, while molybdenum disulfide provides the core wear-resistant and lubricating function, resulting in a composite modified filler with excellent dispersibility. After adding HDPE sheath material, the wear resistance, mechanical strength, dimensional stability, UV aging resistance, and flame retardant properties of the material are simultaneously improved.
[0017] Preferably, the wollastonite is treated with glass fiber and aluminum silicate.
[0018] By adopting the above technical solutions, wollastonite reduces the molding shrinkage rate of HDPE, improves the dimensional stability of the material, and makes the sheath less prone to warping and deformation under long-term stress and temperature changes. The glass fiber embedded in the wollastonite system compensates for the insufficient modulus and tensile strength of wollastonite, significantly improving the load-bearing capacity of the sheath and making it less prone to deformation under long-term wind pressure and cable self-weight alternating loads. The interlacing of glass fiber and needle-like wollastonite bridges microcracks under external forces, preventing crack propagation and improving the problems of thermal cycling and vibration fatigue cracking. The rigid surface of the glass fiber, combined with wollastonite, enhances the sheath's scratch resistance and abrasion resistance.
[0019] Aluminum silicate is adsorbed onto the surfaces of wollastonite and glass fiber, and the two are firmly bonded together into an integrated particle by hydrogen bonds of hydroxyl groups, preventing the separation and agglomeration of the wollastonite and glass fiber phases. The aluminum silicate coating on the outer layer of the composite filler reduces the interfacial tension between the inorganic filler and the non-polar HDPE resin, reduces voids at the filler-resin interface, improves interfacial bonding, and alleviates the problem of reduced impact toughness caused by the filler.
[0020] Wollastonite alone offers weak reinforcement and poor interface properties, while glass fiber alone tends to agglomerate and float, resulting in poor bonding with resin. Aluminum silicate alone provides no reinforcement or low shrinkage. Aluminum silicate, acting as an intermediate binder, firmly bonds pretreated glass fiber to the wollastonite surface, forming an integrated composite filler. This combines the advantages of wollastonite's low shrinkage and creep resistance, glass fiber's high strength and modulus, and aluminum silicate's improved interface and weather resistance / flame retardancy. When added to HDPE bridge sheathing material, it simultaneously improves material strength, dimensional stability, wear resistance, aging resistance, and flame retardancy while maintaining the low-temperature high toughness provided by POE.
[0021] Preferably, the ultraviolet absorber is UV-327 ultraviolet absorber.
[0022] By adopting the above technical solution, UV-327 ultraviolet absorber can efficiently absorb harmful outdoor ultraviolet rays, convert ultraviolet light energy into harmless heat energy release, and block the photoaging reaction of polyethylene. It has high processing thermal stability, is not easily volatilized and lost during extrusion molding, and forms a dual physical and chemical weather-resistant system with carbon black masterbatch. Combined with antioxidant 1010, it synergistically inhibits thermal and photo-oxidative aging, significantly extending the service life of bridge cable sheaths outdoors. It is also resistant to migration and salt spray extraction, making it suitable for all-weather complex outdoor working conditions of bridges.
[0023] Preferably, the flame retardant is a halogen-free magnesium hydroxide flame retardant.
[0024] By adopting the above technical solution, the flame retardant decomposes upon heating, releasing water of crystallization to absorb heat, cool down, and dilute flammable gases. It decomposes to generate magnesium oxide, forming a dense heat-insulating and oxygen-barrier layer, achieving low-smoke, non-toxic flame retardancy. When combined with inorganic fillers such as wollastonite, aluminum silicate, and talc, it can construct a more stable composite flame-retardant barrier layer. At the same time, it is resistant to migration and salt spray, and has good compatibility with HDPE, POE, and weather-resistant additives. While giving the bridge cable sheath flame-retardant properties, it does not impair the material's low-temperature toughness and long-term outdoor weather resistance.
[0025] Secondly, this application also provides a method for preparing high-toughness and weather-resistant HDPE bridge cable sheath material, comprising the following steps: High-density polyethylene, POE ethylene-octene copolymer elastomer, wollastonite, carbon black masterbatch, ultraviolet absorber, antioxidant 1010, and flame retardant are mixed, extruded and granulated to obtain high-toughness and weather-resistant HDPE bridge cable sheath material.
[0026] By adopting the above technical solution, the mixing achieves micro-uniform dispersion of each component, eliminates filler agglomeration and local enrichment defects of additives, and the melt blending allows HDPE to be completely melted, POE elastomer to be fully melted and dispersed, and inorganic fillers and various functional additives to be further refined and dispersed in the melt, eliminating tiny agglomerated particles; at the same time, the resin and modified filler interfaces are fully wetted and bonded, improving the interfacial bonding strength.
[0027] Through an integrated process of mixing, extrusion, and granulation, the advantages of each component are fully synergistic. POE provides low-temperature crack resistance and toughness, while modified wollastonite ensures low shrinkage and creep resistance. Treated carbon black and UV absorbers construct a dual long-term weather-resistant system. Antioxidant 1010 ensures processing and long-term thermal stability. Magnesium hydroxide achieves halogen-free, low-smoke flame retardancy. The overall material combines high toughness, dimensional stability, wear resistance, UV aging resistance, fire resistance, and salt spray corrosion resistance, making it specifically suitable for outdoor all-weather wrapping and protection of long-span bridge cables.
[0028] Preferably, the extrusion granulation temperature is 200-210℃.
[0029] By adopting the above technical solution, the extrusion granulation temperature is 200-210℃. This temperature range allows HDPE and POE to fully melt and achieve uniform blending, ensuring uniform dispersion of inorganic fillers, UV absorbers, antioxidant 1010, and halogen-free magnesium hydroxide flame retardant. At the same time, this temperature is lower than the decomposition temperature of magnesium hydroxide and the thermal decomposition temperature of light stabilizers and antioxidants. During the processing, there is no large amount of water vapor or additive volatilization, avoiding the formation of bubbles in the particles. The toughening, weather resistance, and flame retardant properties of the material are fully preserved, and the extrusion homogenization effect is excellent, making it suitable for large-scale continuous granulation production.
[0030] In summary, this application has the following beneficial effects: 1. The above-mentioned components in this application work together to offset the shortcomings, and the prepared sheath material has multiple properties such as excellent low temperature toughness, low molding shrinkage, long-term UV aging resistance, halogen-free flame retardancy, and resistance to bending fatigue. It is suitable for the requirements of long-span bridge cables and overcomes the defects of traditional single HDPE sheaths such as easy cracking at low temperature, poor weather resistance, lack of flame retardancy, and easy dimensional deformation.
[0031] 2. In this application, wollastonite improves rigidity and dimensional stability, increases flexural modulus and heat distortion temperature, making the sheath less prone to warping and deformation under long-term sun exposure and load, improving the material's wear resistance, compressive strength and creep resistance, and making it less prone to deformation under the long-term effects of cable weight and wind pressure.
[0032] 3. In this application, high-density polyethylene is used as the main body of the sheath material, providing the most basic structural strength, rigidity, heat resistance and excellent electrical insulation. The regular molecular chain and high crystallinity of HDPE give it good tensile strength and resistance to environmental stress cracking. Detailed Implementation
[0033] The present application will be further described in detail below with reference to the embodiments.
[0034] The raw materials used in the examples and comparative examples are all commercially available.
[0035] Preparation Example 1 High-density polyethylene is treated with calcium sulfate whiskers and molybdenum disulfide nanoparticles.
[0036] 40 kg of high-density polyethylene, 10 kg of calcium sulfate whiskers, 1 kg of silane coupling agent KH560, and 5 kg of molybdenum disulfide nanoparticles were mixed and extruded into granules at a temperature of 200°C and a screw speed of 350 r / min to obtain pretreated high-density polyethylene.
[0037] Preparation Example 2 The difference from Preparation Example 1 is that no calcium sulfate whiskers are added during the high-density polyethylene treatment process.
[0038] Preparation Example 3 The difference from Preparation Example 1 is that molybdenum disulfide nanopowder is not added during the high-density polyethylene treatment process.
[0039] Preparation Example 4 Molybdenum disulfide nanoparticles are pretreated with graphene and polyvinylpyrrolidone.
[0040] 0.6 kg of graphene was dispersed in 50 L of ethanol / water mixed solution (ethanol:water = volume ratio 4:6), sonicated for 2 h, 3 kg of molybdenum disulfide nanoparticles and 0.8 kg of polyvinylpyrrolidone were added, filtered, and dried to obtain pretreated molybdenum disulfide nanoparticles.
[0041] Preparation Example 5 The difference from Preparation Example 4 is that no graphene is added during the pretreatment of molybdenum disulfide nanopowder.
[0042] Preparation Example 6 The difference from Preparation Example 4 is that polyvinylpyrrolidone was not added during the pretreatment of molybdenum disulfide nanopowder.
[0043] Preparation Example 7 Wollastonite is treated with glass fiber and aluminum silicate.
[0044] 1 kg of glass fiber was dispersed in 10 L of 1% dilute hydrofluoric acid solution, soaked for 15 min, washed with water, and dried to obtain pretreated glass fiber. Disperse 6 kg of wollastonite into 60 L of deionized water, add 0.5 kg of aluminum silicate, stir for 1.5 h, then add 1 kg of pretreated glass fiber, stir for 2.5 h, filter, and dry to obtain treated wollastonite.
[0045] Preparation Example 8 The difference from Preparation Example 7 is that no glass fiber is added during the wollastonite treatment.
[0046] Preparation Example 9 The difference from Preparation Example 7 is that aluminum silicate is not added during the wollastonite treatment.
[0047] Example 1 A high-toughness and weather-resistant HDPE bridge cable sheath material, by weight, comprises the following raw materials: 50 kg of high-density polyethylene, 10 kg of POE ethylene-octene copolymer elastomer, 4 kg of wollastonite, 4 kg of carbon black masterbatch, 1 kg of ultraviolet absorber, 2 kg of antioxidant 1010, and 5 kg of flame retardant; the ultraviolet absorber is UV-327 ultraviolet absorber, and the flame retardant is halogen-free magnesium hydroxide flame retardant.
[0048] The preparation method of the above-mentioned high-toughness and weather-resistant HDPE bridge cable sheath material includes the following steps: mixing high-density polyethylene, POE ethylene-octene copolymer elastomer, wollastonite, carbon black masterbatch, ultraviolet absorber, antioxidant 1010, and flame retardant, and extruding and granulating to obtain the high-toughness and weather-resistant HDPE bridge cable sheath material. The extrusion granulation temperature is 200℃.
[0049] Example 2: A high-toughness and weather-resistant HDPE bridge cable sheath material, which differs from Example 1 in that, by weight, it includes the following raw materials: 55 kg of high-density polyethylene, 8 kg of POE ethylene-octene copolymer elastomer, 6 kg of wollastonite, 3 kg of carbon black masterbatch, 2 kg of ultraviolet absorber, 3 kg of antioxidant 1010, and 7 kg of flame retardant.
[0050] Example 3: A high-toughness and weather-resistant HDPE bridge cable sheath material, which differs from Example 1 in that the high-density polyethylene is prepared by Preparation Example 1.
[0051] Example 4: A high-toughness and weather-resistant HDPE bridge cable sheath material, which differs from Example 1 in that the high-density polyethylene is prepared by Preparation Example 2.
[0052] Example 5: A high-toughness and weather-resistant HDPE bridge cable sheath material, which differs from Example 1 in that the high-density polyethylene is prepared by Preparation Example 3.
[0053] Example 6: A high-toughness and weather-resistant HDPE bridge cable sheath material, which differs from Example 3 in that the molybdenum disulfide nanopowder is prepared by Example 4.
[0054] Example 7: A high-toughness and weather-resistant HDPE bridge cable sheath material, which differs from Example 3 in that the molybdenum disulfide nanopowder is prepared by Example 5.
[0055] Example 8: A high-toughness and weather-resistant HDPE bridge cable sheath material, which differs from Example 3 in that the molybdenum disulfide nanopowder is prepared by Example 6.
[0056] Example 9: A high-toughness and weather-resistant HDPE bridge cable sheath material, which differs from Example 6 in that the wollastonite is prepared using Preparation Example 7.
[0057] Example 10: A high-toughness, weather-resistant HDPE bridge cable sheath material, which differs from Example 6 in that the wollastonite is prepared using Preparation Example 8.
[0058] Example 11: A high-toughness, weather-resistant HDPE bridge cable sheath material, which differs from Example 6 in that the wollastonite is prepared using Preparation Example 9.
[0059] Comparative Example 1 A high-toughness, weather-resistant HDPE bridge cable sheath material differs from Example 1 in that it does not contain wollastonite.
[0060] The performance of a high-toughness and weather-resistant HDPE bridge cable sheath material prepared in Examples 1-11 and Comparative Example 1 was tested. Tensile strength was tested according to standard GB / T 1701-2001, and abrasion resistance was tested according to standard ASTM G99-04, using the pin-disc friction test method to detect wear rate; thermal aging was performed by aging in an oven at 135℃ for 168 hours and then testing the tensile strength; the test results are shown in Table 1.
[0061] Table 1 Test data for the examples and comparative examples
[0062] As shown in Table 1, the high-toughness and weather-resistant HDPE bridge cable sheath material prepared in Examples 1-2 of this application has good mechanical properties, abrasion resistance, and aging resistance. Specifically, Example 1 has a tensile strength of 30 MPa, a tensile strength after aging of 26 MPa, and an abrasion rate of 2.11 × 10⁻⁶ mm³ / N·n. It is evident that the synergistic combination of the above components results in a sheath material that simultaneously possesses excellent low-temperature toughness, long-lasting UV aging resistance, and halogen-free flame retardancy, making it suitable for the requirements of long-span bridge cables and overcoming the defects of traditional single HDPE sheaths, such as easy cracking at low temperatures, poor weather resistance, and easy dimensional deformation.
[0063] Example 3 involved treating high-density polyethylene with calcium sulfate whiskers and molybdenum disulfide nanoparticles, while Examples 4-5 involved treating high-density polyethylene without adding calcium sulfate whiskers or molybdenum disulfide nanoparticles. Table 1 shows that the tensile strength, post-aging tensile strength, and wear rate of Example 3 were significantly better than those of Example 1, while the corresponding test results of Examples 4-5 were significantly worse than those of Example 3, but better than those of Examples 1-2. This indicates that calcium sulfate whiskers dispersed in the HDPE structure can bridge cracks like a bridge, effectively preventing crack propagation and thus improving the material's impact resistance, mechanical properties, and wear resistance. Molybdenum disulfide nanoparticles significantly reduce the friction coefficient and wear rate of HDPE, making the material more scratch-resistant, increasing the degradation temperature of HDPE, providing high toughness at low temperatures, and reducing cracking under high and low temperature cycling.
[0064] Example 6: Molybdenum disulfide nanopowder was pretreated with graphene and polyvinylpyrrolidone (PVP). Examples 7-8: Molybdenum disulfide nanopowder was treated without the addition of graphene and PPVP, respectively. Table 1 shows that the tensile strength, post-aging tensile strength, and wear rate of Example 6 were significantly better than those of Example 3. The corresponding test results of Examples 7-8 were significantly worse than those of Example 6, but better than those of Example 3. This indicates that uniformly dispersed molybdenum disulfide nanopowder deposits or anchors on the surface of graphene sheets, preventing agglomeration between molybdenum disulfide nanopowder particles, improving the interfacial bonding between the composite filler and HDPE / POE resin, and enhancing the overall tensile and flexural strength. The polar groups on the PPVP molecular chain can be firmly adsorbed onto the surface of the molybdenum disulfide nanopowder, allowing the PPVP-modified molybdenum disulfide nanopowder to better adhere to the graphene sheets, thus jointly improving the comprehensive performance of the HDPE composite material.
[0065] Example 9 involved treating wollastonite with glass fiber and aluminosilicate, while Examples 10-11 involved treating wollastonite without adding glass fiber or aluminosilicate. Table 1 shows that Example 9 exhibited significantly better tensile strength, post-aging tensile strength, and wear rate results than Example 6. Examples 10-11 showed significantly worse results than Example 9, but still better than Example 6. This indicates that aluminosilicate is adsorbed onto the surfaces of wollastonite and glass fiber, and the two are firmly bonded into integrated particles via hydroxyl hydrogen bonds. This prevents the separation and agglomeration of the wollastonite and glass fiber phases, reduces voids at the filler-resin interface, improves interfacial bonding, and alleviates the impact toughness reduction caused by the filler.
[0066] Comparative Example 1, without the addition of wollastonite, showed significantly worse tensile strength, tensile strength after aging, and wear rate test results compared to Examples 1-2, as can be seen from Table 1. This indicates that wollastonite improves rigidity and dimensional stability, increases flexural modulus and heat distortion temperature, making the sheath less prone to warping and deformation under long-term sun exposure and load, and improving the material's wear resistance and compressive strength, thus preventing deformation under the long-term effects of cable weight and wind pressure.
[0067] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A high-toughness, weather-resistant HDPE bridge cable sheath material, characterized in that, By weight, it includes the following raw materials: 50-55 parts high-density polyethylene, 8-10 parts POE ethylene-octene copolymer elastomer, 4-6 parts wollastonite, 3-4 parts carbon black masterbatch, 1-2 parts ultraviolet absorber, 2-3 parts antioxidant 1010, and 5-7 parts flame retardant.
2. The high-toughness, weather-resistant HDPE bridge cable sheath material according to claim 1, characterized in that, The high-density polyethylene is treated with calcium sulfate whiskers and molybdenum disulfide nanoparticles.
3. The high-toughness, weather-resistant HDPE bridge cable sheath material according to claim 2, characterized in that, The molybdenum disulfide nanopowder was pretreated with graphene and polyvinylpyrrolidone.
4. The high-toughness, weather-resistant HDPE bridge cable sheath material according to claim 1, characterized in that, The wollastonite is treated with glass fiber and aluminum silicate.
5. The high-toughness, weather-resistant HDPE bridge cable sheath material according to claim 1, characterized in that, The ultraviolet absorber is UV-327 ultraviolet absorber.
6. The high-toughness, weather-resistant HDPE bridge cable sheath material according to claim 1, characterized in that, The flame retardant is a halogen-free magnesium hydroxide flame retardant.
7. The method for preparing a high-toughness, weather-resistant HDPE bridge cable sheath material according to claim 1, characterized in that, Includes the following steps: High-density polyethylene, POE ethylene-octene copolymer elastomer, wollastonite, carbon black masterbatch, ultraviolet absorber, antioxidant 1010, and flame retardant are mixed, extruded and granulated to obtain high-toughness and weather-resistant HDPE bridge cable sheath material.
8. The method for preparing a high-toughness, weather-resistant HDPE bridge cable sheath material according to claim 7, characterized in that, The extrusion granulation temperature is 200-210℃.